2018
DOI: 10.2147/jpr.s156938
|View full text |Cite
|
Sign up to set email alerts
|

Coprescribing proton-pump inhibitors with nonsteroidal anti-inflammatory drugs: risks versus benefits

Abstract: Nonsteroidal anti-inflammatory drugs (NSAIDs) are often coadministered with proton-pump inhibitors (PPIs) to reduce NSAID-induced gastrointestinal (GI) adverse events. This coadministration is generally regarded as safe, and is included in many of the guidelines on NSAID prescription. However, recent evidence indicates that the GI risks associated with NSAIDs can be potentiated when they are combined with PPIs. This review discusses the GI effects and complications of NSAIDs and how PPIs may potentiate these e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
61
0
13

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(79 citation statements)
references
References 99 publications
2
61
0
13
Order By: Relevance
“…84 However, lower GI bleeding could be not protected by PPIs, 2 and emerging evidences further indicate that PPI may increase the risk of NSAIDs induced small bowel damage and bleeding. 70,85,86 A similar exacerbation of NSAIDs induced small bowel damage was also observed in H2 receptor antagonists. 85 It was suggested that long term use of PPIs may exacerbate NSAIDs induced small bowel injury by altering intestinal microbiota (dysbiosis) following acid suppression, 7,70 which is supported by small intestinal bacterial overgrowth observed in patients with long-term use of PPIs.…”
Section: Role Of Ppissupporting
confidence: 56%
“…84 However, lower GI bleeding could be not protected by PPIs, 2 and emerging evidences further indicate that PPI may increase the risk of NSAIDs induced small bowel damage and bleeding. 70,85,86 A similar exacerbation of NSAIDs induced small bowel damage was also observed in H2 receptor antagonists. 85 It was suggested that long term use of PPIs may exacerbate NSAIDs induced small bowel injury by altering intestinal microbiota (dysbiosis) following acid suppression, 7,70 which is supported by small intestinal bacterial overgrowth observed in patients with long-term use of PPIs.…”
Section: Role Of Ppissupporting
confidence: 56%
“…Das Spektrum der gastrointestinalen Nebenwirkungen einer NSAR Therapie ist breit und reicht von gastrointestinaler (GI) Refluxerkrankung bis zur Ulkusblutung und -perforation. Eine Prophylaxe von GI Nebenwirkungen sollte kann durch Protonenpumpeninhibitoren (PPI) oder die Wahl eines selektiven COX2 Inhibitors erreicht werden [38]. Die Indikation für eine PPI Prophylaxe orientiert sich dabei am individuellen Risiko für eine GI Nebenwirkung, wobei bei moderatem Risiko ( ≥ 1 zutreffend: > 65 J, unkomplizierte Ulzera, Therapie mit ASS bzw.…”
Section: Nozizeptive Schmerzen Bei Rheumatologischen Erkrankungenunclassified
“…Da für PPI selbst ein ungünstiges Nebenwirkungsprofil bekannt ist, z. B. eine Erhöhung des Risikos für Frakturen, Demenz und renaler Erkrankung [38], muss auch die Indikation zur PPI Therapie mit Bedacht gestellt werden. Auch zu beachten ist, dass PPI nicht vor Ulzerationen im unteren GI Trakt schützen, die unter NSAR Therapie ebenfalls häufig auftreten [41].…”
Section: Nozizeptive Schmerzen Bei Rheumatologischen Erkrankungenunclassified
See 1 more Smart Citation
“…The literature identifies a number of specific risk factors for GI toxicity, and it would appear reasonable to use gastroprotection in these circumstances 12…”
Section: Indicationsmentioning
confidence: 99%